Work-Family Conflict Assesment: Instrument Validity and Reliability Testing Using the Rasch Model - Denia Syapitri; Daharnis Daharnis; Zadrian Ardi (Universitas Negeri Padang, 2025)
Work-family conflict (WFC) is a psychosocial problem that arises due to a mismatch between work and family role demands, which impacts an individual's psychological well-being. The high impact of WFC requires the availability of accurate, valid, and reliable measurement instruments. This study aims to test the validity and reliability of the Work-Family Conflict instrument using the Rasch Model. The study involved 60 married working women respondents. The instrument was developed based on the Greenhaus and Beutell framework, which includes time-based, strain-based, and behavior-based conflict dimensions with a Likert response format. Data analysis was conducted using Winsteps software to evaluate item suitability, reliability, and unidimensionality. The results showed that 19 of the 22 items were declared valid, item reliability was very high (0.94-0.95), and the unidimensionality assumption was met, although there was overlap in the middle response category. Overall, the instrument has good psychometric quality and is relevant for use in the context of Guidance and Counseling.